Step 1

Name the two equations as (1) and (2),

3x-y+5=0...(1)

2x+3y-4=0...(2)

Reframe equation (1) in the form y=mx+c

y=3x+5...(3)

Step 2

Substitute equation (3) in equation (2) and solve for x,

2x+3(3x+5)-4=0

2x+9x+15-4=0

11x+11=0

\(\displaystyle{x}=-\frac{{11}}{{11}}\)

x=-1

Step 3

Substitute value of x in equation (3),

y=3(-1)+5

y=2

Step 4

Hence the solution to the system of equations above is (-1,2)

Name the two equations as (1) and (2),

3x-y+5=0...(1)

2x+3y-4=0...(2)

Reframe equation (1) in the form y=mx+c

y=3x+5...(3)

Step 2

Substitute equation (3) in equation (2) and solve for x,

2x+3(3x+5)-4=0

2x+9x+15-4=0

11x+11=0

\(\displaystyle{x}=-\frac{{11}}{{11}}\)

x=-1

Step 3

Substitute value of x in equation (3),

y=3(-1)+5

y=2

Step 4

Hence the solution to the system of equations above is (-1,2)